Effect of foot-and-mouth disease virus 3C protease B2 β-strand proline mutagenesis on expression and processing of the P1 polypeptide using a plasmid expression vector. (31st January 2019) - Martel, Erica; Forzono, Emily; Kurker, Richard; Clark, Benjamin A.; Neilan, John G.; Puckette, Michael
Abstract : The production of experimental molecular vaccines against foot-and-mouth disease virus utilizes the viral encoded 3C protease for processing of the P1 polyprotein. Expression of wild type 3C protease is detrimental to host cells. The molecular vaccine constructs containing the 3C protease L127P mutant significantly reduce adverse effects associated with protease expression while retaining the ability to process and assemble virus-like particles. In published 3C protease crystal structures, the L127 residue is contained within the B2 β-strand as part of the A2 –B2 β-sheet. To provide insight into the mechanism by which the L127P mutant alters the properties of the 3C protease, we performed scanning proline mutagenesis of residues 123–128 of the B2 β-strand and monitored expression and P1 processing. Simultaneously, we utilized random mutagenesis of the full 3C sequence to identify additional mutations presenting a phenotype similar to the L127P mutation. Six of the tested mutants enhanced expression over wild type, and the I22P, T100P and V124P mutations surpassed the L127P mutation in certain cell lines. These data areinterpreted in conjunction with published 3C protease crystal structures to provide insight into the mechanism by which these mutations enhance expression.